Spaghettis: an array based algorithm for similarity queries in metric spaces - Chavez, E.; Marroquin, J.L.; Baeza-Yates, R. (String Processing and Information Retrieval Symposium and International Workshop on Groupware : September 22-24, 1999, Cancun, Mexico, 1999)
We present a new, pivot based data structure with dynamic capabilities to insert/delete both database elements and pivots. This feature is useful for applications where the database is not stationary, and the pivots must be changed from time to time. The spaghettis data structure can be thought of as a "flat" representation of a tree; but unlike it, a full representation of the distances can be used, instead of discretizing them.